Identifying the roles of imine and alkyne linkages in determining the photocatalytic hydrogen evolution over thiadiazole-based covalent organic frameworks. Issue 39 (16th September 2022) - Hao, Lei; Huang, Kaihui; Wang, Ningxin; Shen, Rongchen; Chen, Shuling; Bi, Weiling; Li, Neng; Zhang, Peng; Li, Youji; Li, Xin
Abstract : The imine-linked thiadiazole-based COF exhibits much better photocatalytic H2 evolution than the alkyne-linked COF, due to more efficient separation, faster transport and higher reducing ability of photogenerated electrons in imine-linked COF. Abstract : Covalent organic frameworks (COFs) have emerged as an extremely promising material for photocatalytic water splitting for hydrogen production. However, their photocatalytic performance is seriously affected by the properties of their donors, acceptors and linkages. So far, few studies have been reported on the key roles of the linkages of a specific COF in improving its photocatalytic hydrogen production performance. Herein, this study designed and synthesized two thiadiazole-based COFs linked by imine and alkyne bonds. The results show that the photocatalytic hydrogen production performance of imine-linked COFs (TeTz–COF1) is 19.6 times higher than that of alkyne-linked COFs (TeTz–COF2). Impressively, TeTz–COF1 achieves an apparent quantum efficiency of 3.5% at 475 nm due to the presence of imine bonds. The experimental results confirm that TeTz–COF1 with imine linkages shows higher photocurrent density, lower photocurrent resistance, and longer fluorescence lifetime than TeTz–COF2 with alkyne linkages. Meanwhile, the well-defined density functional theory (DFT) calculations further suggest that both the imine bond and the acetylene bond belong to the HOMO orbitals. Particularly, the imine bonds endow TeTz–COF1 with more delocalized orbital occupation and smaller work functions, thus leading to its lower excited state energy, stronger carrier separation ability and faster electron migration capability. Both theoretical analysis and the experimental results prove that the presence of imine bonds in TeTz–COF1 can enable the efficient separation and fast transport of photogenerated carriers and high reducing ability of photogenerated electrons. This work may provide important guiding significance for the development of new COFs in the direction of photocatalytic water splitting for hydrogen production.